Concrete Failure Modeling Based on Micromechanical Approach Subjected to Static Loading - Endah Wahyuni (IPTEK The Journal for Technology and Science, 2010)
In this paper, a micromechanical model based on the Mori-Tanaka method and the spring-layer model is developed to study the stress-strain behavior of concrete. The concrete is modeled as a two-phase composite. And the failure of concrete is categorized as mortar failure and interface failure. The research presents a method for estimating the modulus of concrete under its whole loading process. The proposed micromechanical model owns the good capabilities for predicting the entire response of concrete under uniaxial compression. It is suitable that tensile strain is as the criterion of concrete failure and the prediction of crack direction also fits with experimental phenomenon.